Pengaruh Kualitas Pelayanan dan Fasilitas Kesehatan Terhadap KepuasanPasien Rawat Inap Ruang Anggrek (Studi Kasus Rumah Sakit Umum Daerah dr. Chasbullah Abdulmadjid Kota Bekasi) - Putri Maryani Supranoto; Suparman Suparman (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study entitled "The Effect of Quality of Health Services and Health Facilities on Satisfaction of Inpatients at the Orchid Room" which was compiled by Putri Maryani Supranoto with NPM: CB117112163. This study aims to determine: 1) whether the quality of service affects the satisfaction of inpatients in the orchid room, 2) whether the quality of service affects the satisfaction of inpatients in the orchid room, 3) whether the quality of services and health facilities affect the satisfaction of inpatients in the orchid room. . The population in this study were inpatients in the orchid room with a sample of 363 people. The method used is a survey with a quantitative approach. The sampling technique used is non-probability sampling. The instrument testing technique in this study used validity and reliability tests, while the data analysis techniques used were descriptive analysis, multiple linear analysis, and classical assumption tests. The results of the study show that: 1) service quality affects patient satisfaction with t_count (6,486) > t_table (1.971), 2) Health facilities affect patient satisfaction with t_count values (9,691) > t_table (1.971), 3) service quality and Health facilities have an effect on patient satisfaction with the value of F_count (125,250) > F_(table )(3,04). Based on the value of R^2, the quality of service and health facilities with a percentage of 65.5% affects patient satisfaction